Zoonotic Agents in Feral Pigeons (Columba livia) from Costa Rica: Possible Improvements to Diminish Contagion Risks - Torres Mejía, Ana María (2018)
Most studies on zoonotic agents in pigeons have been conducted in the Palearctic region, but the scarcity of data is notorious in the Neotropical region, where these birds can breed all year around and are in close contact with humans. In this study, we used a combination of culture-dependent and culture-independent methods to identify infectious agents in 141 fecal samples from pigeons collected at four urban parks from Costa Rica. Of these we identified 34 positive samples for Salmonella enterica subsp. enterica serovar Braenderup (24.1%), 13 for Chlamydophila psittaci (9.2%), 9 for enteropathogenic Escherichia coli (6.4% eaeA, 0% stx-1 and 0% stx-2), and 2 for Campylobacter jejuni (1.4%). These populations of pigeons pose low risk for healthy adult humans, however, they may pose a health risk to immunocompromised patients or children. This study provides scientific data, which can be incorporated into educational programs aiming to reverse the public attitude toward pigeon feeding and to rationally justify population control efforts.